International financial policy : essays in honor of Jacques J. Polak - Polak, J. J.; Frenkel, Jacob A.; Goldstein, Morris (Washington, D.C. : Internatioanl Monetary Fund, 1991)
The book is about Jacques J. Polak's outstanding contributions to international economics and his distinguished service at the International Monetary Fund, the IMF and De Nederlandsche Bank documented during a conference organized in his honour.
Published in association with De Nederlandsche Bank.
Includes bibliographical references.
opc 30/08/2016
Loans
Keywords: International finance..; International Monetary Fund